2017
DOI: 10.7287/peerj.preprints.3177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of an RNA interference (RNAi) gene knockdown protocol in the anaerobic gut fungus Pecoramyces ruminantium strain C1A

Abstract: Members of the anaerobic gut fungi (AGF) reside in rumen, hindgut, and feces of ruminant and non-ruminant herbivorous mammals and reptilian herbivores. No protocols for gene insertion, deletion, silencing, or mutation are currently available for the AGF, rendering gene-targeted molecular biological manipulations unfeasible. Here, we developed and optimized an RNA interference (RNAi)-based protocol for targeted gene silencing in the anaerobic gut fungus Pecoramyces ruminantium strain C1A. Analysis of the C1A ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Isolation of AGF taxa enables taxonomic, metabolic, physiological and ultrastructural characterization of individual taxa. As well, cultures availability enables subsequent—omics, synthetic and system‐biology, and biogeography‐based investigations (Couger et al ., 2015; Seppälä et al ., 2016; Haitjema et al ., 2017; Calkins et al ., 2018; Henske et al ., 2018a; Henske et al ., 2018b; Murphy et al ., 2019), as well as evaluation of evolutionary processes underpinning speciation in the AGF (Youssef et al ., 2013; Wang et al ., 2019). However, efforts to isolate and maintain AGF strains have lagged behind their aerobic counterparts mainly due to their strict anaerobic nature and the lack of reliable long‐term storage procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of AGF taxa enables taxonomic, metabolic, physiological and ultrastructural characterization of individual taxa. As well, cultures availability enables subsequent—omics, synthetic and system‐biology, and biogeography‐based investigations (Couger et al ., 2015; Seppälä et al ., 2016; Haitjema et al ., 2017; Calkins et al ., 2018; Henske et al ., 2018a; Henske et al ., 2018b; Murphy et al ., 2019), as well as evaluation of evolutionary processes underpinning speciation in the AGF (Youssef et al ., 2013; Wang et al ., 2019). However, efforts to isolate and maintain AGF strains have lagged behind their aerobic counterparts mainly due to their strict anaerobic nature and the lack of reliable long‐term storage procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Whisson et al [21] generated 11 transgenic lines of plant‐pathogenic Phytophthora infestans with reduced gfp expression through the delivery of dsRNA into the protoplast, which resulted in a significant decrease in gfp expression (7%–67%) for 17 days after treatment with dsRNA compared to the control lines. In a more recent study, Calkins et al [22] developed an RNA interference (RNAi)‐based protocol for targeted gene knockdown in the anaerobic gut fungus Pecoramyces ruminantium using exogenous addition of synthetic double‐stranded siRNAs into germinating spores and found that the highest inhibition levels were obtained with 100 nM siRNA. Therefore, this technique seems to be a feasible method that can be quickly and easily applied to the study of gene function in the entomopathogenic fungus B. bassiana .…”
Section: Introductionmentioning
confidence: 99%